Échos allemands à une école de théologie: le Saulchoir (1939-1941) - Quisinsky, Michael (Revue des sciences philosophiques et théologiques, 2010)
The debate generated by Marie-Dominique Chenu’s pamphlet, Une école de théologie : le Saulchoir, printed pro manuscripto in 1937, clearly indicates that the work did not go unnoticed. In Germany, it aroused the interest of three theologians from different theological backgrounds. In his 1939 review, Friedrich Stegmüller praises the book’s advocacy of a moderate theological pluralism. In 1941, Odo Casel argues that Chenu’s theology reconnects with the finest theological tradition, particularly the christocentrism and pneumatological dimension of the patristic period. In 1939, Alfons Deissler, who would later become professor of Old Testament at Freiburg im Breisgau, wrote a thesis on the theological method of Martin Gerbert (1720-1793), the abbot-prince of St Blasien in the Black Forest. Rather surprisingly, he concludes his thesis by connecting Gerbert’s intuitions with those of Chenu. In so doing, he refers to a theological challenge of the utmost importance: namely, the way in which the Augustinian and Thomist traditions complement each other in the life of the Church.